Integration of Transcriptomics and Metabolomics Reveals the Responses of Sugar Beet to Continuous Cropping Obstacle - Huang, Weijuan; Sun, Donglei; Wang, Ronghua; An, Yuxing (Frontiers in Plant Science, 2021)
Sugar beet is vulnerable to years of continuous cropping, and allelopathy is one of the important factors leading to continuous cropping disorder. To explore the physiological and molecular mechanisms behind continuous cropping obstacle on sugar beet, this study combined transcriptomics and metabolomics to analyze the effects of different years of continuous cropping on metabolite changes, differential gene expression, and root exudate regulation in sugar beet. We collected sugar beet root samples from 1-year, 3-year, and 5-year continuous cropping systems for metabolome and transcriptome analyses. Our data revealed that T3 and T5 had 50 and 33 metabolites significantly different from T1, respectively. The autotoxic substance salicylaldehyde was found to continuously accumulate in root exudates with increasing years of continuous cropping. Sucrose was highly reduced in T3 (4.05-fold decrease) and T5 (2.01-fold decrease) compared to T1. Respectively, 2660 and 3515 differentially expressed genes (DEGs) were significantly regulated in T3 and T5 compared to T1. KEGG enrichment analyses showed that metabolic pathways and biosynthesis of secondary metabolites were perturbed in T3 and T5 versus T1. Integrated metabolomics analyses identified 73 DEGs involved in enriched metabolic pathways, all of which were the oxidation-reduction process pathway. In conclusion, this study provides evidence that continuous cropping obstacle can change the metabolome and transcriptome of sugar beet, impacting its growth and quality.